Priest Anđelko Nešić (1870–1941): Narative Sketch for the Portrait of a Priest in Kosovo Vilayet - Jovanović, Luka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper deals with the national activites of the Mitrovica priest Anđelko Nešić (1870–1941) during the last decades of the Ottoman Empire rule in Old Serbia. Although in the service of religion, his activity is primarily national, aimed at protecting the Serbian people and serving the interests of the Kingdom of Serbia in the Kosovo Vilayet. The paper covers the chronological period until the beginning of the First Balkan War in 1912.